PENGEMBANGAN PESTISIDA NABATI BERBASIS DAUN SIRSAK (Annona muricata) DAN SERAI (Cymbopogon citratus) UNTUK MENDUKUNG KEWIRAUSAHAAN BERKELANJUTAN PETANI LOKAL - Natalia Kristiani Lase; Della Howu Howu Zendrato; Lilis Sartika Gulo; Ridho Victory Nazara (Universitas Nias Raya, 2025)
This community service program was carried out with the main objective of reducing farmers’ dependence on chemical pesticides by introducing and training them in the production of botanical pesticides made from soursop leaves (Annona muricata) and lemongrass (Cymbopogon citratus). The program was implemented in Dusun II Bakaru, Siwalubanua I Village, Gunungsitoli Idanoi District, in collaboration with the Tanjung Morawa Farmers Group as the primary partner. The activities were systematically designed through several stages, including socialization about the negative impacts of chemical pesticides, training in the preparation of botanical pesticides, field assistance during application, and evaluation of the results. During implementation, farmers showed great enthusiasm in participating in every training session. Based on the evaluation results, farmers’ understanding of the benefits and working mechanisms of botanical pesticides increased by 85%. Moreover, the application of these natural pesticides successfully reduced pest attack intensity by up to 70%, which had a positive impact on crop yields. This activity not only provided ecological benefits by reducing chemical residues in the environment but also fostered entrepreneurial awareness among farmers. Several participants even began developing small-scale businesses to produce botanical pesticides independently. Thus, this community service program has made a tangible contribution to realizing sustainable agriculture, enhancing farmers’ self-reliance, and promoting the utilization of local resources as a new economic potential for rural communities.